Representasi Budaya Tionghoa dalam Film Kung Fu Panda 4: Analisis Semiotika Roland Barthes - Dewi Utari, Yosephina Agitya Intan; Delijar, Ressi Maulidina (Ideas Publishing, 2024)
Representation is the use of signs that can be symbolized by image, writing, and sound. Representation is related to culture and there are tools to represent culture, through films, which is the Kung Fu Panda 4 movie. The purpose of this research is to determine the represent ation of Chinese culture in the Kung Fu Panda 4 movie. The method used is descriptive qualitative with Roland Barthes' semiotic analysis and observation techniques in the Kung Fu Panda 4 movie. The research results show the strong Chinese culture in the Kung Fu Panda 4 movie, which is packaged in a sign and symbol, and the meaning of cultural symbols can be found.